Parliamentary committee systems : conference report, Dhaka, 27-28 May 1999. - Conference on Comparative Constitutional Law: Parliamentary Committee Systems (1999 : Dhaka, Bangladesh); Institute of Parliamentary Studies (Bangladesh) (Dhaka : Bangladesh Jatiya Sangsad, Institute of Parliamentary Studies, 1999)
Contributed articles presented at the Conference on Comparative Constitutional Law: Parliamentary Committee Systems.
Includes prefatory matters, an article, and press clippings in Bengali.
Keywords: Legislative bodies -- Committees -- Congresses; Bangladesh. -- Jātīẏa Saṃsada -- Committees -- Congresses